Sunday bloody Sunday [videorecording (DVD)] - Schlesinger, John, 1926-2003; Jackson, Glenda; Finch, Peter, 1916-1977; Head, Murray; Ashcroft, Peggy, 1907-1991; Britton, Tony (Criterion collection, 2012)
Depicts the romantic lives of two Londoners, a middle-aged doctor and a prickly thirty something divorcee who are sleeping with the same handsome young artist. A revelation in its day, this may be the 1970s most intelligent, multitextured film about the complexities of romantic relationships; it is keenly acted and sensitively directed, from a penetrating screenplay.